Analisis Pentingnya Suatu Sistem terhadap Jaminan Sosial bagi Para Tenaga Kerja - Zakia Arikinanti; Enjum Jumhana; Desriama Peronika Sihite; Analisa Br Gurusinga; Yuliastuti Yuliastuti (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
Social security for workers is very important, and can aim to create welfare for workers and their families. An effective social security system can not only provide protection against risks, such as the risk of work accidents, illness or other things. There are laws that have been in effect, which discuss this. Implementation of a good social security system can increase the productivity of the workforce. Not only that, it can also aim to reduce social inequality and create very harmonious industrial relations between the two parties. Of course, in that case, it is not free from challenges, the main challenge is the implementation of this system, namely the awareness of informal workers about the importance of protection from this guarantee. Not only that, compliance in employers can also register their employees in this program. Therefore, synergy between the government and related institutions is needed.